ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SEKTOR PERTAMBANGAN DI INDONESIA DAN MALAYSIA - Alexander Anggono; Farhan Syahriza; Firda Ivana Amelia (Jurnal Kajian Akuntansi dan Auditing, 2022)
This study is intended to compare the financial performance of mining companies in Indonesia and Malaysia from 2014-2019. In particular, to analyze financial performance of mining companies in both countries by applying liquidity ratios, profitability ratios, activity ratios, and market ratios. The comparison is conducted as many investors interested to invest in mining sectors, and both countries are having the similar potential and market characteristics. The number of samples employed in this study is 23 mining sector companies in Indonesia and 11 mining sector companies in Malaysia. The data is analyzed using the multiple regression equations (F-test and T-test) and the two-sample difference test (U Mann Whitney test). The findings of this research are: (1) the debt to equity (DER) significantly affects the financial performance of mining sector companies in Indonesia; (2) The variables current ratio (CR) and price to earnings ratio (PER) have a significant influence on the financial performance of mining sector companies in Malaysia; (3) The variables current ratio (X1), debt to equity ratio (X2), Total assets turnover (X3), price to earnings ratio (X4), and return on equity (X5) have an effect on the financial performance of mining sector companies in Indonesia and in Malaysia; and (4) there is no significant difference in financial performance between mining companies in Indonesia and Malaysia. The implication of this study is to assist investors to opt the best investment opportunity in mining sector in Indonesia and Malaysia stock market.